A Course module for science, technology, and society - Alata, Eden Joy Pastor; Calano, Mark Joseph Tumada ;Pawilen, Greg Tabios (Manila, Philippines : Rex Book Store, 2021)
This module was prepared to aid undergraduate students cultivate their 21st century learning.
Chapter 1 : General concepts and historical developments of science, technology, and society -- Chapter 2 : The role of science and technology in nation-building -- Chapter 3 : Science, technology, society, and the human condition -- Chapter 4 : Specific issues in science, technology, and society.
Includes bibliographical references.
Keywords: SCIENCE -- SOCIAL ASPECTS